Biblical Exegesis and Systematic Theology: Toward Mutual Benefit - Huijgen, Arnold (Journal of reformed theology, 2022)
Notwithstanding the legitimate distinction between biblical studies and systematic theology, these disciplines can and should benefit from each other. On the one hand, biblical studies deals with texts that make claims about God that are read primarily in a liturgical context by people with a faith commitment. Accordingly, while the distantiation of an academic approach is helpful, a systematic theological dimension enriches the otherwise rather naturalistic biblical studies. On the other hand, systematic theology needs biblical studies. Historical Christian theology shows that abstract theology without engagement with biblical studies becomes arid. Current emphases on history, language, narrative, and Israel offer opportunities to connect the two disciplines. This article sketches a methodology for the mutual benefit of biblical studies and systematic theology.